The antimicrobial effect behind Cannabis sativa - Laureano Schofs; Mónica D. Sparo; Sergio F. Sánchez Bruni (Wiley, 2021)
Abstract The development of multidrug‐resistant bacteria has revealed the need for new antimicrobial compounds. Cannabis sativa preparations have a long history of medical applications, including the treatment of infectious diseases. This review collects the information about the activity of C. sativa extracts and its main components (cannabinoids and terpenes) against pathogenic bacteria and fungus, to assess its potential using as antimicrobial agents.